Perspectives on short break destinations and their contribution to local-regional economic development: a literature review - Hamann, Antonieta; Hernani-Merino, Martin; Tarazona Vargas, Enver Gerald (Universidad de Talca, 2022)
Globalization and changing lifestyles are generating new forms of tourism, including visits to short break destinations. The objective of this study is to propose a definition of short break destinations and to present the dimensions of the attractiveness of tourist destinations. The methodology consisted of reviewing the literature of 64 academic publications. The result shows the determinants that should be considered in the definition of short break destination and the following dimension are proposed: 1) naturals resources, 2) cultural and historical resources, 3) social factors, 4) tourist services and 5) infrastructure.

La globalización y los cambios en los estilos de vida están generando nuevas formas de turismo, entre las que se encuentran las visitas a destinos de corta estadía. El objetivo de este estudio es proponer una definición de los destinos de corta estadía y presenter las dimensiones del atractivo de los destinos turísticos. La metodología consistió en la revision de literatura de 64 publicaciones académicas. Los resultados muestran los determinantes que se deben considerar en la definición del destino de corta estadía y se proponen las siguientes dimensiones: 1) recursos naturales, 2) recursos culturales e históricos, 3) factores sociales, 4) servicios turísticos y 5) infraestructura.
Keywords: Short break; City break; Corta estadía; Tourist destinations; Escapada urbana; Destinos turísticos; Dimensions of a tourist destination; Dimensiones de un destino turístico; https://purl.org/pe-repo/ocde/ford#5.02.04